Estimating size at first maturity (L50) from Gonadossomatic Index (GSI) data - Nelson F. Fontoura; Aloísio S. Braun; Paulo Cesar C. Milani (Neotropical Ichthyology)
Correct estimates of size at first maturity (L50) are useful for fish stock management and different methods have been proposed. In this study we propose the use of a modified logistic to estimate L50, including a variable asymptote (A). We also test the use of the Gonadossomatic Index (GSI) as a flag to establish the reproductive status of each female fish. The method is demonstrated using GSI data for four Neotropical fish species: Characiformes: Astyanax fasciatus (n = 473) and Oligosarcus robustus (n = 297); Siluriformes: Loricariichthys anus (n = 427) and Trachelyopterus lucenai (n = 195). The results were stable enough to propose this method be used for other fish species with different life histories and with a relatively unconstrained sampling programs. Nevertheless, a wide scale test program is desirable to identify any possible bias in this approach.